REMEDIASI MISKONSEPSI SISWA MATERI HUKUM NEWTON MENGGUNAKAN MODELQUANTUM TEACHINGDI SMPN 3 SEMPARUK - Deviani, Nur Rastie; Djudin, Tomo; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to find out the effectiviness of quantum teaching method in remediation of students’ misconception in newton law material at SMP Negeri 3 Semparuk. Pre-experimental design with one group pretest-posttest design was used in this research. Sample of this research was students of VIII B class (n=24) who was choosen by intact group random sampling technique. This research used diagnostic test which consists of 8 multiple choise question with open reasoning. Based ondata analysis, the result as: the average decrease of misconceptions equal to 43,09%,  and the level effectiveness of remediation was in the middle (DQM=50,92%). Based on there results, it was expected that quantum teaching method can be used as an alternative remediation activities to overcome students’ misconception.Keywords: Misconception, Remediation, quantum teaching method, Newton’s law